2008
DOI: 10.1007/s11104-008-9756-4
|View full text |Cite
|
Sign up to set email alerts
|

Nodulation of native woody legumes in Hong Kong, China

Abstract: Woody legumes can play an important role in forest restoration on degraded land but the knowledge of woody legumes has lagged behind their uses. This study is a pioneer investigation to explore the ability of native woody legumes to form root nodules and fix nitrogen in Hong Kong. Nine sites of different habitat types were surveyed during both wet and dry seasons for two years. Young plants of woody legumes along studied transects were excavated. The patterns of nodulation and nodule morphology were recorded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…These coralloid nodules are hypothesised to be older nodules that have become partially indeterminate and are exhibiting new bacterial colonisation and nodule cell division. It has been previously noted in several studies that most tree legumes tend to have woody indeterminate nodules [3,28,34]. We conclude that pongamia nodulation at first leads to determinate-type nodules and often progresses later into an indeterminate state.…”
Section: Characterisation Of the Pongamia Nodulesupporting
confidence: 58%
See 1 more Smart Citation
“…These coralloid nodules are hypothesised to be older nodules that have become partially indeterminate and are exhibiting new bacterial colonisation and nodule cell division. It has been previously noted in several studies that most tree legumes tend to have woody indeterminate nodules [3,28,34]. We conclude that pongamia nodulation at first leads to determinate-type nodules and often progresses later into an indeterminate state.…”
Section: Characterisation Of the Pongamia Nodulesupporting
confidence: 58%
“…As previously mentioned, indeterminate nodules are to be found on most woody legumes. A survey of wild legumes in China by Ng and Nau [28] observed spherical nodules on all legume species; however, these nodules were thought to be undifferentiated and immature, if nodules of other shapes were also observed. This idea of globular nodules turning into cylindrical indeterminate nodules is not new.…”
Section: Characterisation Of the Pongamia Nodulementioning
confidence: 99%
“…This complicates the precise evaluation of %Ndfa (Boddey et al, ; Unkovich, ; Unkovich et al, ). Therefore, we validated the method by comparing our results with published data of nitrogenase activity by Ng and Hau (). Comparisons showed that %Ndfa appeared to be a good proxy for BNF ability, as for the majority of the legumes the difference in δ 15 N with their neighbours was significant and consistent with laboratory analysis of nitrogenase activity by Ng and Hau ().…”
Section: Methodsmentioning
confidence: 77%
“…Biological nitrogen fixation (BNF) by legumes is considered a major source of soil nitrogen (N), in addition to atmospheric deposition (Galloway et al, ), bacterial and fungal nitrification (Peix, Ramírez‐bahena, Velázquez, Peix, & Ram, ) and geochemical weathering (Holloway & Dahlgren, ). Much research has been carried out to quantify and understand BNF in both natural (Ng & Hau, ; Nichols, Rosemeyer, Carpenter, & Kettler, ; Vitousek, Menge, Reed, & Cleveland, ) and agricultural systems (Unkovich et al, ). For example, by intercropping, N‐fixing soybeans can supply N to adjacent plants directly via root exudates and root decomposition and further facilitate phosphorus (P) mobilization by mycorrhizal activities (Govindarajulu et al, ; Klein, Siegwolf, & Körner, ; Liu, Wu, Baddeley, & Watson, ; Mulder, Jumpponen, Högberg, & Huss‐Danell, ; Paynel, Murray, & Cliquet, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation